Analisis Kebijakan Pemerintah Daerah dalam Mengembangkan Pariwisata Mada Oi Tampuro Kecamatan Sanggar Kabupaten Bima - Wira Purdiawan Putra; Taufik Firmanto; Gufran (Jurnal Hukum Lex Generalis, 2025)
Mada Oi Tampuro tourism has significant potential as a leading destination in Bima Regency. However, its development still faces several structural and policy obstacles. This article analyzes the local government's policies in supporting tourism development in the area. The results indicate that the policies are not yet optimally integrated between planning, regulation, and community empowerment. It concludes that synergy between stakeholders, institutional strengthening, and sustainable infrastructure development are crucial.